Design and Development of Augmented Reality Applications in Computer Network Topology Animation - Suprianto, Gaguk (Jurnal Jaringan Telekomunikasi, 2024)
Technology can be applied in the development of teaching materials to enable students to explore material outside the classroom. One of the relevant technologies is Augmented Reality (AR), which allows the appearance of three-dimensional objects in the real world. One of the courses that has significance in the realm of information and communication technology is computer networks. However, this course faces several obstacles in implementing the teaching and learning process, including high equipment costs and expensive maintenance requirements. In addition, the teaching methods currently used still tend to be monotonous. Given these factors, the objective of this study is to incorporate Augmented Reality technology into the teaching of computer network courses. An Augmented Reality application has been developed and tested using the black box method. This approach has the advantage of assessing software quality, ensuring that the software meets desired expectations Test results on mobile devices state that the application developed can be installed on two mobile devices with different specifications. The marker test was also declared successful up to a distance of 100 cm. All buttons and features in the application run smoothly and function well. The application designed and developed possesses the potential for use in additional courses necessitating object visualization. In addition, the developed application supports users with special needs because there are audio features in each material. For future research, it may be considered to use a markless-based method because it is more flexible and does not require markers.